Development of the nervous system in the early hatching larvae of the ctenophore Mnemiopsis leidyi. (26th July 2021) - Norekian, Tigran P.; Moroz, Leonid L.
Abstract: Ctenophores are descendants of an early branching basal metazoan lineage, which may have evolved neurons and muscles independently from other animals. Mnemiopsis is one of the important reference ctenophore species. However, little is known about its neuromuscular organization. Here, we mapped and tracked the development of the neural and muscular elements in the early hatching cydippid larvae, as well as adult Mnemiopsis leidyi . The overall development of the neuromuscular system in Mnemiopsis was very similar to Pleurobrachia bachei, although in Mnemiopsis the entire process occurred significantly faster. The subepithelial neural cells were observed immediately after hatching. This population consisted of a dozen of separated individual neurons with short neurites. In about 2 days, when their neurites grew significantly longer and connected to their neighbors, they began to form a canonical polygonal subepithelial network. Mesogleal neural elements prominent in all studied adult ctenophores were not detectable in Mnemiopsis larvae but were clearly labeled in closely related Lobata species Bolinopsis infundibulum . Hatched larvae also had putative mechanoreceptors with long stereocilia and approximately two dozen muscle cells. In adult Mnemiopsis, the feeding lobes and auricles contained two distinct populations of neurons and neural ensembles that were not observed in other ctenophore lineages and likely represented elaborate neuronal innovations characteristic for the clade Lobata and their lifestyles. Abstract : The enigmatic ctenophore neural system might evolve independently from other animals. The analysis of neurodevelopment in Mnemiopsis (an important reference species for the phylum) revealed that neural cells were labeled immediately after larval hatching (arrows in the image) and several days later begin to form a neural network. In adult Mnemiopsis, the feeding lobes and auricles contain two distinct populations of neurons and neural ensembles that are not observed in other ctenophore lineages and represent elaborate neuronal innovations characteristic for clade Lobata and their lifestyles.